Identification of hub genes correlated with tumor-associated M1-like macrophage infiltration in soft tissue sarcomas - Lv, Minchao; He, Feixiong; Guo, Jinku; Zheng, Zhenxin; Wang, Wei; Xie, Jun (Frontiers in Genetics, 2022)
Soft tissue sarcomas (STS) were a heterogeneous series of tumors that might result in severe disability and death. Tumor-associated M1-like macrophages infiltration played a critical role in tumor development and progression. This study aimed at identifying the hub genes associated with M1-like macrophages infiltration in STS cells. Firstly, the expression profiles from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) database were imported to calculate the level of M1-like macrophages infiltration by CIBERSORTx. Afterwards, the Kaplan-Meier survival analysis was performed to evaluate the correlation between macrophage infiltration and prognosis. Then, weighted gene co-expression network analysis (WGCNA) and protein-protein interaction analysis of GEO data was applied to identify the key gene related with M1-like macrophages infiltration, followed by the functional analysis using TCGA cohort to validate downstream signaling associated with that. Finally, pan-cancer analysis was conducted to investigate the gene function in other type of tumors. We found LCK expression positively related to M1-like macrophages infiltration level and it positively regulated the expression level of genes regulated to macrophage polarization, including interferon-γ (INF-γ), interleukin-12 (IL12), tumor necrosis factor (TNF), PI3K, NF-κB, and CXCL9, 10, 11. In summary, a ‘LCK- INF-γ/IL-12-TNF/PI3K-NF-κB’ axis might exist in STS cells that regulated M1-like macrophage infiltration.